Characteristics of Factors Influencing the Occurrence of Cleft Lip and/or Palate: A Case Analysis and Literature Review - Małgorzata Kulesa-Mrowiecka; Anna Lipowicz; Bożena Anna Marszałek-Kruk; Damian Kania; Wojciech Wolański; Andrzej Myśliwiec; Krzysztof Dowgierd (MDPI AG, 2024)
Introduction: Cleft lip with or without cleft palate (CL/P) stands as the most common congenital facial anomaly, stemming from multifactorial causes. Objective: Our study aimed to ascertain the prevalence and characteristics of cleft palates, identify associated risk factors to inform prevention and prenatal detection for early intervention, and assess postoperative rehabilitation protocols for cleft palates. Design: This study employs a retrospective descriptive and clinical approach. Patients: The study includes 103 children with cleft palates treated at the Department of Head and Neck Surgery Clinic for Children and Young Adults, Department of Clinical Pediatrics, University of Warmia and Mazury. Methods: We conducted a thorough evaluation of records, considering variables such as sex, cleft type, maternal occupation, parental education, and family history of clefts. Data analysis was carried out using R software version GPL-3 and ordinal logistic regression analyses. Results: Notably, children born to mothers who experienced significant stress during pregnancy exhibited a 9.4-fold increase in the odds of having bilateral cleft palates. Conversely, no substantial evidence was found to support the influence of the child's sex, birth order, body mass, maternal exposure to workplace toxins, infections, or drug toxicity on the dependent variable. Conclusions: Our findings suggest that children with parents who have a history of clefts and those with less educated mothers are more likely to develop bilateral cleft palates. Additionally, children born to mothers experiencing stress during pregnancy face an increased risk of bilateral cleft palates. It is important to note that there is a paucity of literature on rehabilitation following various cleft palate surgical techniques in children.